INDEPENDENT STUDY FOR IMPROVING ENGLISH SKILLS OF NON-ENGLISH DEPARTMENT STUDENTS - Rahayu, Pipit (JEE (Journal of English Education), 2015)
This article is concerned with the analysis of an independent study in improving English proficiency of students of non-English Department in FKIP University of Pasir Pengaraian on the basis of a recent study. The aspects explored in the study covered activities done by the students in their independent study and their proficiency. Generally, independent study can be conducted anywhere and at anytime by using any supporting sources such as language laboratory, library and Self Access centre. The research employed the descriptive qualitative design and the instruments used in collecting the data were a set of questionnaire and tests.The data analysis covered preparation and data implementation. The findings showed that the activities of independent study done by non-English department students were reading English newspapers and magazines, listening to the radio especially English programmes, watching videos, and making use of language laboratory, library, self access centre. The finding also provided the evidence that the students’ English proficiency showed significant improvement.